(untitled) (Polis (Santiago), 2021)
In recent years, small-scale agricultural producers have experienced strong changes that have prevented them from carrying out their agricultural activities adequately; worse still, public policies have driven them to lag behind and abandon their lands. This research is based on a study of self-perception, under the narrative of how peasants conceive themselves in the face of changes due to neoliberalism and the reasons for their persistence to continue working in the field in defense of their territory. As a result, it is found that the role of small-scale farmers is essential for local and regional development since there are more social, cultural, and environmental functions that they fulfill, beyond the merely economic ones.